Cloudina-Corumbella-Namacalathus association from the Itapucumi Group, Paraguay: Increasing ecosystem complexity and tiering at the end of the Ediacaran - Warren, Lucas Veríssimo (2017)
The intriguing Ediacaran fossil Namacalathus is described from limestones of the Tagatiya Guazú Formation, Itapucumi Group, Paraguay. This is the fifth occurrence of the genus in the Ediacaran geological record. The Paraguayan Namacalathus specimens are preserved as partially complete spheroidal cups with an opening at the top and thin walled stems. The remains of this soft-calcified globe-shaped organism occur as sparse disarticulated parautochthonous fragments within bioclastic deposits dominated by Cloudina shells with subordinate Corumbella fragments. The co-occurrence of these three skeletal metazoan species in the same environmental context attests that the diversity of the Paraguayan accumulations is ecologically comparable to the typical skeletal assemblage of the Nama Group. The discovery of new samples of Namacalathus in the Itapucumi Group also indicates that this genus presented a broader paleobiogeographic distribution than previously thought and, in the same way as Cloudina, it represents a low latitude, shallow water metazoan of the Ediacaran Gondwana.